NOSE-TO-BRAIN DELIVERY, A ROUTE OF CHOICE FOR TARGETING BRAIN TUMORS - SHEHU, IBRAHIM AMINU; ISLAM, MOJAHIDUL; SINGH, VIJENDER (International Journal of Applied Pharmaceutics, 2021)
Brain tumours are the most lethal type of cancer, which is difficult to manage due to the inherent suboptimal bioavailability of the chemotherapy agent at tumour sites, consequent of high levels of protection of physiological blood-brain barrier (BBB), blood tumour barrier (BTB) and blood-cerebrospinal fluid barrier (CSF). Improving the permeability of these barriers would enhance the disease's clinical prognosis and promote patients' quality of life. To this end, scientists have conducted several studies to determine the most suitable route for CNS delivery. Most of which show that the nose-to-brain is proposed to be the most convenient, efficacious and clinically beneficial non-invasive means of delivering chemotherapeutic agents directly to the brain. Therefore, this study compares the therapeutic benefits of intranasal and other conventional brain delivery systems and further evaluates the clinical benefits of using different nanocarriers for brain tumour targeting. However, we surveyed the literature by conducting an in-depth search of the research keywords and their combinations in recognized scientific databases, primarily Science Direct, PubMed, Google Scholar, and Research Gate. Our findings have shown that the nose-to-brain delivery of chemotherapeutics is a breakthrough in bypassing the effects of BBB, BTB, and CSF barriers, improving the delivery of drugs to the brain for specific tumour targeting with desired clinical prognosis.